Pengaruh Intellectual Capital, Kepemilikan Manajerial dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perbankan - Nafisa Rosella; Dwiyanjana Santyo Nugroho (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This study aims to test and analyze the effect of Intellectual Capital, Managerial Ownership, Company Size on the financial performance of banks listed on the Indonesia Stock Exchange in the period 2020-2022. This type of research is quantitative research. This research was conducted on banking sector companies listed on the Indonesia Stock Exchange using purposive sampling method obtained a total of 20 best companies according to Forbes in 2022. The data analysis technique used is multiple linear regression test. The results of this study indicate that Managerial Ownership, Company Size has a positive and significant effect on financial performance. While Intellectual Capital has no effect on financial performance. This study only consists of three independent variables, namely Intellectual Capital, Managerial Ownership, Company Size, while there are many other factors that influence financial performance that are not examined.